1955
DOI: 10.1103/physrev.97.142
|View full text |Cite
|
Sign up to set email alerts
|

Gamma and X-Radiation in the Decay ofAm241

Abstract: takes into consideration the energy dependent effect of the detection efficiency and the effect of the constant "window width" of the scintillation spectrometer, the present data indicates that the 138-kev 7 ray is considerably stronger, and the 77-kev x-ray much weaker than measured by Jensen et al 7 This is consistent with the recent work by Schardt et al*The dotted curve in fig. 3 represents the summing spectrum obtained with the sample in the phosphor. The As K x-rays arising from K capture were cut off by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1956
1956
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…From a correlation of data available on relative abundances of L x-rays in the region of Z~92, 17 it is found that L a x-rays arise predominantly from the filling of Lin shell vacancies, while L$ and L y x-rays are produced from the filling of a combination of L-shell vacancies. As first noted by James et at., 2 the relative L x-ray intensities associated with the L capture of Np 235 indicate a large fraction of Xm-shell vacancies.…”
Section: Discussionmentioning
confidence: 99%
“…From a correlation of data available on relative abundances of L x-rays in the region of Z~92, 17 it is found that L a x-rays arise predominantly from the filling of Lin shell vacancies, while L$ and L y x-rays are produced from the filling of a combination of L-shell vacancies. As first noted by James et at., 2 the relative L x-ray intensities associated with the L capture of Np 235 indicate a large fraction of Xm-shell vacancies.…”
Section: Discussionmentioning
confidence: 99%
“…Taking the Kα 2 for example, the transition energy is 97068.18 eV compared with the experimental result 97069±3 eV of Barreau et al [22] For the transition rates of these lines, the results presented are smaller than the other ones, which may due to including the Breit interaction and QED effects in the calculations. In order to compare with the measured spectra, [24] our transition rates of K X-rays are convoluted into a Gaussian line shape of broadening 600 eV and plotted in Fig. 1.…”
Section: Transition Energies Transition Rates Linesmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21] Barreau et al [22] and Ahmad et al [23] measured energies, natural widths and intensities of Np K X-rays, respectively. Jaffe et al [24] and Day [25] analyzed the L X-rays of Np following the decay of 241 Am for the first time. Weksler et al [26] measured transition energies of L lines associated with α-decay of 241 Am with a high-resolution Si (Li) spectrometer.…”
Section: Introductionmentioning
confidence: 99%
“…Because in the work of Jaffe et al 1 the Li and Ln conversion electrons from this gamma ray were not…”
Section: Introductionmentioning
confidence: 97%
“…1 discuss the unusual properties of the 59.6-kev state in Np 237 , which is populated by more than 99% of the Am 241 disintegrations. They measured the total conversion coefficient of the 59.6-kev gamma ray to be 0.92, and concluded that the radiation is electric dipole.…”
Section: Introductionmentioning
confidence: 98%